A Retrospective Analysis of 54 Patients underwent Rigid Bronchoscopy - Sağıroğlu, Gönül (Fırat University, 2011)
Objective: We aim to analyze the surgical and anesthesiological perspective of patients underwent rigid bronchoscopy via general anesthesia. Materials and Methods: Between January 2009 and November 2009, 54 patients underwent rigid bronchoscopy were retrospectively analyzed. Patient's demographic features, co-morbidities, indication of procedures, complications, type of stent and the length of both anesthesia and surgery were analyzed. Induction anesthesia was performed with prophofol and vecuronium; intubation was undertaken by rigid bronchoscopy. Subsequently, intermediate positive pressure with 100% oxygen was delivered through the standard circuit connected to rigid bronchoscope. Results: 40 male and 14 female patients were underwent rigid bronchoscopy under general anesthesia with the mean age was 54 (14–81). The indications were malignant disease (n=35), postintubation stenosis (n=8), tracheomalasia (n=4), hemoptysis (n=4), endobronchial tuberculosis (n=2) and foreign body (n=1). The surgical procedures performed through rigid bronchoscope were; tumor destruction in 18, stenting in 12, biopsy in 11, stent removal in 4, aspiration of thick and purulent secretion in 3, hemoptysis in 2, dilatation for further stenting in one, foreign body removal in one, tumor destruction and biopsy in one and tumor destruction and stenting in one patient. The types of stents were 6 covered metallic stent and 7 silicone Y type stent. The mean duration of surgery and anesthesia was 38 (10±115) min and 48 (20±125) min respectively. Conclusion: Bronchoscopic management in patients with tracheal stenosis is safe and sufficient. The most important issue during anesthesia is to provide adequate ventilation and oxygenation. Key words: tracheabronchial obstruction, rigid bronchoscopy, tracheabronchial

Amaç: Çalışmamızda genel anestezi altında rijit bronkoskopi uygulanan olguları hasta özellikleri, anestezi ve cerrahi açısından sunmayı amaçladık. Gereç ve Yöntem: Ocak 2009-Kasım 2009 tarihleri arasında genel anestezi ile girişimsel bronkoskopi uygulanan 54 olgu retrospektif olarak incelendi. Olguların demografik özellikleri, yandaş hastalıkları, bronkoskopi endikasyonları, neoadjuvan tedavi gören olgu sayısı, rijit bronkoskopide yapılan uygulamalar, girişim sırasında karşılaşılan komplikasyonlar, stent tipleri, genel anestezi süresi ve cerrahi süre kaydedildi. Anestezi indüksiyon ve idamesinde propofol ve vekuronyum uygulandı ve rijit bronkoskop ile entübasyon yapıldı. Standart anestezi devresi rijit bronkoskopun yan girişine bağlandı ve aralıklı pozitif basınçla %100 oksijen ile ventilasyon sağlandı. Bulgular: Yaş ortalaması 54 (14–81) yıl olan olguların 40'ı erkek 14'ü kadındı. Bronkoskopi endikasyonları malignite (n=35), postentübasyon stenoz (n=8), trakeomalazi (n=4), hemoptizi (n=4), endobronşial tüberküloz (n=2), yabancı cisim (n=1) idi. Rijit bronkoskopide yapılan uygulamalar 18 tümör destrüksiyonu, 12 stent implantasyonu, 11 biyopsi, 4 stent çıkarılması, 3 pürülan sekresyon aspirasyonu, 2 hemoptizi aspirasyonu, 1 stent dilatasyonu, 1 yabancı cisim çıkarılması, 1 tümör destrüksiyonu ve biyopsi, 1 tümör destrüksiyonu ve stent dilatasyonu idi. Girişim sırasında karşılaşılan komplikasyonlar hipoksi (n=23), hipertansiyon (n=19), taşikardi (n=13), pnömotoraks (n=1) idi. Stent tipleri 6 metalik covered stent ve 7 silikon Y tipi stent idi. Genel anestezi süresi ortalama 48 (20±125) dk, cerrahi süre ise ortalama 38 (10±115) dk olarak bulundu. Sonuç: Trakeal stenozların tedavisinde bronkoskopik tedavi yöntemleri hastalar için etkili ve güvenlidir. Anestezi açısından yeterli ventilasyon ve oksjenasyon sağlamak en önemli konudur.
Rijit Bronkoskopi Uygulanan 54 Olgunun Retrospektif Analizi